Clinical characteristics of patients with atypical teratoid/rhabdoid tumors: a monocentric retrospective analysis - Wang, Zhiliang; Yang, Jingchen; Liu, Xing; Liu, Wei (Frontiers in Pediatrics, 2025)
PurposeAtypical teratoid/rhabdoid tumors (ATRTs) are very rare, highly malignant embryonal neoplasms in central nervous system. The aim of this study was to conduct a retrospective analysis of ATRT patient survival and investigate the prognostic factors associated with ATRT.MethodsA retrospective study was conducted using information of patients who received treatment between 2016 and 2021 in Beijing Tiantan Hospital. Kaplan–Meier curves were used for overall survival (OS) analysis. Univariate and multivariate COX analyses were applied for OS predicting.Results20 histologically confirmed ATRT patients were included. The majority were male (75%) and aged over 3 years (65%). 71.4% of patients under 3 years and 46.2% of above 3 years had supratentorial tumors. All patients underwent surgery, with 60% having total resections, primarily in the supratentorial region. Subsequent treatment involved varying chemotherapy and radiation combinations, with 40% of patients receiving it, and 87.5% of those were older than 3 years, The median overall survival for ATRT patients was 180 days. Survival differed significantly between patients under and above 3 years. Radiotherapy increased overall survival for all patients. Univariate and multivariate analysis showed better survival for those diagnosed above age 3 and with adjuvant radiation.ConclusionsPatients older than 3 years old had better prognosis and radiotherapy had a significant effect on improving patient prognosis.